Use of a Sendai virus-based vector for effcient transduction of pinniped fbroblasts - V. R. Beklemisheva; A. G. Menzorov (Вавиловский журнал генетики и селекции, 2019)
Generation of induced pluripotent stem (iPS) cells expanded possibilities of pluripotency and early development studies. Generation of order Carnivora iPS cells from dog (Canis lupus familiaris), snow leopard (Panthera uncia), and American mink (Neovison vison) was previously reported. The aim of the current study was to examine conditions of pinniped fbroblast reprogramming. Pinnipeds are representatives of the suborder Caniformia sharing conservative genomes. There are several ways to deliver reprogramming transcription factors: RNA, proteins, plasmids, viral vectors etc. The most eﬀective delivery systems for mouse and human cells are based on viral vectors. We compared a lentiviral vector which integrates into the genome and a Sendai virusbased vector, CytoTune EmGFP Sendai Fluorescence Reporter. The main advantage of Sendai virusbased vectors is that they do not integrate into the genome. We performed delivery of genetic constructions carrying ﬂuorescent proteins to fbroblasts of seven Pinnipeds: northern fur seal (Callorhinus ursinus), Steller sea lion (Eumetopias jubatus), walrus (Odobenus rosmarus), bearded seal (Erignathus barbatus), Baikal seal (Pusa sibirica), ringed seal (Phoca hispida), and spotted seal (Phoca largha). We also transduced American mink (N. vison), human (Homo sapiens), and mouse (Mus musculus) fbroblasts as a control. We showed that the Sendai virusbased transduction system provides transgene expression onetwo orders of magnitude higher than the lentiviral system at a comparable multiplicity of infection. Also, transgene expression after Sendai virusbased transduction is quite stable and changes only slightly at day four compared to day two. These data allow us to suggest that Sendai virusbased vectors are preferable for generation of Pinniped iPS cells.